2017
DOI: 10.1590/2317-6369000009216
|View full text |Cite
|
Sign up to set email alerts
|

Riscos ocupacionais e adesão a precauções-padrão no trabalho de enfermagem em terapia intensiva: percepções de trabalhadores

Abstract: Introduction: working at intensive care units leads to great exposure to occupational hazards. Objectives: to know how intensive care nursing workers perceive occupational hazards and Standard Precautions (SP), as well as to describe factors that may interfere with the adherence to the recommended SP. Method: qualitative, descriptive, and exploratory study conducted between July and September 2015 involving twelve nursing workers from two intensive care units. Semi-structured interviews and thematic content an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 22 publications
0
7
0
14
Order By: Relevance
“…In addition, as a team leader, the nurse must act properly and in a way that the other members can mirror their conduct when handling the necessary measures for the safety of patients and workers. 14 It was also observed that 75.0% of the nurses work in shifts of 12 consecutive hours, characterizing an extensive and tiring day, mainly for dealing with patients who require intensive, uninterrupted and complex care. This fact becomes more significant when one considers that the work overload is a facilitating condition for errors and accidents related to the profession.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, as a team leader, the nurse must act properly and in a way that the other members can mirror their conduct when handling the necessary measures for the safety of patients and workers. 14 It was also observed that 75.0% of the nurses work in shifts of 12 consecutive hours, characterizing an extensive and tiring day, mainly for dealing with patients who require intensive, uninterrupted and complex care. This fact becomes more significant when one considers that the work overload is a facilitating condition for errors and accidents related to the profession.…”
Section: Discussionmentioning
confidence: 99%
“…11 In emergency care, the professional usually opts for immediate care of the patient, relegating his personal protection into second place and being even more exposed to occupational accidents. 14 Thus, in addition to ensuring an adequate number of nurses so that their tasks can be carried out without haste and constantly reinforcing the importance of standard precautions measures, it is recommended to make available the recommended PPE in strategic and easily accessible locations to improve adherence to its use. 20 Another point to be emphasized in the professionals' knowledge (SPKQ) is the hygiene of the hands.…”
Section: /16mentioning
confidence: 99%
See 1 more Smart Citation
“…Poor adherence to PPE can be related to the occupational risk perception deficit, low accountability and insufficient feedback from leaders regarding the importance of safety practices. 23 It was evident from the data that the institution has complied with the labor regulations related to the supply of PPE, 9 however, the participants pointed to the lack of commitment and neglect regarding the use of PPE.…”
Section: More Attention Especially By Those Who Do Not Discard Matermentioning
confidence: 99%
“…exposição constante aos riscos organizacionais, com trabalhos em turnos alternados, jornadas extensas, cobranças, produtividade e mecanismos de coerção e punição agravam a saúde do enfermeiro e de sua equipe, que estão, sempre, em estado de vigilância para não errar.Diante de todos os dados e de várias pesquisas realizadas sobre os motivos que favorecem os acidentes de trabalho de enfermeiros nos hospitais, vê-se a necessidade urgente de implantar propostas a fim de evitar que os dados anteriormente mencionados aumentem. O trabalho cumpre sua função social quando também produz qualidade de vida para o trabalhador(NAZARIO, CAMPONOGARA, DIAS, 2017). Qmentum (Qualidade Internacional); de Acreditação Hospitalar (ONA, níveis 1, 2 e 3); Hospital Amigo da Criança(UNICEF, 2003); 1º e 2º lugares Prêmio JOHNSON & JOHNSON de Administração Hospitalar; Hospital Sentinela (ANVISA);Maternidade participante do Programa Nacional de Humanização do Parto; Hospital Integrante ao PNAHSH -Programa Nacional de Humanização dos Serviços Hospitalares (Ministério da Saúde), dentre outros.…”
unclassified